Analysis of Labor Absorption in the Jabodetabek Sector Urban Transportation Policy Integration Commuterline Train in Jakarta City - Alifia Barunawati; Farida Rahmawati (Institute of Computer Science (IOCS), 2022)
This research aims to carry out an analysis related to the effect of employment in the Jabodetabek sector. Urban Transportation Policy Integration of commuterline trains in Jakarta and its surroundings. Jabodetabek Urban Transportation Policy Integration is a government study on transportation problems in Jakarta and its surroundings, one of which is in the form of commuterline trains that have existed since 2007. So with this research study, the government has a choice in making decisions to develop and overcome the problems of public transportation facilities in Jakarta and its surroundings. Later, the policy can have a positive impact and provide jobs for residents in Jakarta and its surroundings. The method used is a quantitative approach with a cross-sectional data regression model. The data used in this study uses secondary data taken from data on the number of workers in the commuterline train sector, the number of KRL fleets, the number of KRL routes, and the number of KRL passengers in 2018. The results show that the number of KRL fleets and the number of KRL routes significantly influence. On the employment of the commuterline train sector in Jakarta and its surroundings, while the number of KRL passengers does not significantly affect the employment of the commuterline train sector.